Population dynamics of Callinectes sapidus fishery resource in Lake Maracaibo, Venezuela - Guerrero-Ríos, Randi; Andrade, Glenys; Hernández, Nancy; Ferrer, Orlando; Barrios-Garrido, Héctor (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The blue crab, Callinectes sapidus, supports one of the most significant fisheries in Lake Maracaibo and western Venezuela, although several previous studies suggest signs of overexploitation. This study analyzed the population dynamics of the species as a basis for resource management, based on 46 monthly samples of landings at the main ports of Lake Maracaibo from 2010 to 2014. Monthly length-frequency data were analyzed using the FiSAT II software to estimate growth parameters (ELEFAN I), mortality (length-converted catch curve) and recruitment (cohort analysis). Natural mortality was estimated using several methods due to its complexity. The estimated growth parameters were =14.67 cm, and K = 0.87 yr-1, with higher growth rates in males. Recruitment was continuous, with peaks during the rainy season. Total mortality was estimated at 7.74 yr-1, natural mortality ranged from 0.87 and 2.05 yr-1, and fishing mortality from 5.79 and 6.87 yr-1, showing strong fishing pressure, mainly on females. It was determined that C. sapidus has a short life cycle, with first entry into the fishery at 7-8 months of age and 7.0 cm, remaining until 24 months of age and 12 cm. The catch curve suggests full recruitment between 12 and 13 months of age and 8.7 cm. It is concluded that the high fishing intensity has altered the population structure and limits the adequate renewal of the stock, highlighting the need to strengthen management measures.